Olympic Champions 1896-1936 - the first 40 years - - Reber, B.
This site is dedicated to the 2,006 men and 114 women who brought great pride to their nations when they became Olympic champions. Most may have passed on with the years but their achievements live on in Olympic history. From James Connolly who triple-jumped to the first Gold medal on 6 April 1896 to the German riders who completed their courses on 16 August 1936, the early Olympic Games provided 1,138 occasions of drama, excitement and passion. 35 nations have produced Olympic champions during that time and their names and short biographies are recorded on the following pages.